Advances in molecular and cell biology. - Danielsson, Bengt, 1921-1997; Bulow, Leif (Advances in molecular and cell biology, 1996)
In December 1992, the Department of Pure and Applied Biochemistry at the Chemical Center in Lund, Sweden, organized an international meeting, the Mosbach Symposium on Biochemical Technology, to celebrate the 60th birthday of professor Klaus Mosbach, one of the founders of modern biotechnology. The history of Pure and Applied Biochemistry had its start in 1970, a couple of years after the foundation of the Chemical Center. Klaus Mosbach has been its professor and head of Pure and Applied Biochemistry since its start. During the 1980's he also maintained a professorship at the ETH in Z & uuml;rich, Switzerland. Professor Mosbach is internationally well-known and he has world-leading position within the field of immobilization of bioactive substances and cells as well as affinity chromatography. In 1990, Professor Mosbach was awarded the gold medal by the Royal Swedish Academy of Engineering Sciences for his contributions to biotechnology, especially on the immobilization of bioactive substances. The research activities of the Department of Pure and Applied Biochemistry cover a broad area, such as affinity and separation techniques, bioprocess control, biosensors, development of new carriers and new immobilization procedures for small molecules as well as proteins and cells, including animal and plant cells, gene technology, processes based on immobilized biocatalysts, and construction of organic polymers with enzyme-like properties. The hallmark of the department is its diversified research that generates considerable synergistic effects that are manifested by many new techniques and concepts emanating from the laboratory during the last 20 years. Several of these are marketed by various biotechnology companies. At this meeting we therefore arranged for some of the world's leading experts in biochemistry and biotechnology to give lectures. The topics covered comprise enzyme technology, immobilization of enzymes and cells, abzymes, metabolic engineering, biosensors, and molecular recognition. The official gift from the symposium committee and the participants is this "Festschrift" which covers several important fields of research within the area of biochemical technology. We have made a very unusual approach and have let the "hero of the occasion" present the history of his research